Cardiac myxoma with atypical localization in the right atrium - D.V. Dobrianskyi; P.F. Dudka; M.I. Zahorodnyi; V.Yu. Kuznetsova; R.V. Korolyova; I.P. Tarchenko; Z.O. Dubovenko; T.V. Mykhailevska; O.I. Paraguz (Infusion & Chemotherapy)
ABSTRACT. The article summarizes the main information on the epidemiology, clinical symptoms and diagnosis of cardiac myxoma (CM). CM is a rather rare disease, which is why there is a lack of practical experience among medical professionals. The most frequent localization of CM is the left atrium (over 76 % of cases). An important point in the diagnosis of CM is a careful assessment of clinical signs, including congestive heart failure, embolic, cardialgia and arrhythmic syndromes. The most characteristic symptoms of left-sided CM are shortness of breath during physical exertion, paroxysmal nocturnal dyspnea and pulmonary edema, while in right-sided localization ‒ shortness of breath, edema of the lower extremities, hepatomegaly and ascites. Left atrial myxomas are highly associated with an increased risk of systemic embolization, right atrial myxomas can lead to pulmonary embolism.